Legal Certainty of State Land as an Object of Waqf - Muhammad Ferdynan Alfareza; Herlindah; Supriyadi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
This research aims to critically analyze the legal certainty of state land as a waqf object within the Indonesian legal system, particularly regarding the legal position of the state as the holder of the right to control land and the validity of the Waqf Pledge Deed over state-controlled land. This study employs a normative legal research method using statutory and conceptual approaches. The legal materials consist of primary legal sources in the form of agrarian and waqf-related legislation, secondary legal sources including books, journals, and expert opinions, and tertiary legal materials supporting the analysis. The findings demonstrate that the state does not possess legal standing as a waqif because the state’s right to control land constitutes a public authority to regulate and administer land rather than a proprietary right within private law. Consequently, state land cannot directly become an object of waqf without the prior granting of land rights. Furthermore, the validity of a Waqf Pledge Deed concerning state land is highly dependent on the legal status of the land. Such a deed may be deemed invalid if it is established over pure state land that has not been subject to specific land rights, as it fails to fulfill the ownership requirement of the waqif. The novelty of this research lies in its analysis of the normative conflict between agrarian law and waqf law concerning the legality of state land as a waqf object, as well as in clarifying the limits of state authority in land waqf practices in Indonesia.